Política estadual de saúde mental e a rede de atenção de saúde mental : o caso Espirito Santo - narrando estória e construindo a história - César, Márcia Peixoto (2011)
The assistance offered to individuals with mental disorder and drug users have historically been marked by exclusive processes of segregation and isolation. Currently mental suffering has been more in evidence, because has been acquiring significant proportions in contemporary society, demanding from the authorities to formulate policies that can give concrete evidence of this problem, supporting a more holistic and humane care for this population. This study aims to trace the trajectory of the Mental Health State Policy of Espirito Santo and the Network of Care for Persons with Mental Disorder and Users of Alcohol and Other Drugs. Methodology: For this, there will be an exploratory, descriptive, documentary and literature with a qualitative approach. The scenario: the documents and literature from the State Department of Health, the subject, the managers: Secretaries of Health and Mental Health Coordinator, (since) the 1990s to today. The study will consist of two steps: data collection and interviews. The primary data will be collected through the interview technique, semi-structured, applied to these managers; the secondary will be obtained from official documents (State Health Plans, management reports and other documents that emerge as relevant.) The interviews will be transcribed and narrated in story form, in chronological order of events, enriched by the documents. Results: The state policy of integral attention in mental health to users of alcohol and other drugs of State has been implementing now with advances sometimes with setbacks. The attention network to patients with mental disorder and users of SPAS of the state, despite being built and gradually bringing benefits to the population, is still insufficient to meet the actual need of the state population that accesses to the network. Therefore it is concluded that is necessary to review the operation of this policy, networking and funding, greater integration of public institutions with training institutions, agencies and sectors that constitute the state and the community together to discuss the reality of mental health in the state As well as increased investment in human resources with training and continuing education.